Resenha em foco: um estudo pragmático e contemporâneo sobre o gênero nas revistas Bravo!, Rolling Stone Brasil e Cult - Gonçalves, Carlos Alessandro de Mesquita (2018)
The purpose of this thesis is to identify the structural features of the reviews elaborated by the teams of the Bravo!, Rolling Stone Brazil and Cult magazines in order to broaden the theories about the subject. The three are among the main publications aimed at covering the Brazilian cultural segment. At first, the genre took the marks of the academic segment to mass media, but acquired its own nuances over the years. There are 52 texts published by the magazines as a corpus. They presented diversified compositions, thematic contents and styles. Each publication was followed through 13 editions, which corresponds to the period of one year and one month. Concepts of authors who have worked on academic and journalistic reviews have served as the starting point for this survey. On the communication side, we consulted Coelho (2007), Marques de Melo (2003) and Piza (2013), among others. On the scientific side, we consulted Severino (2000), Maia (2007), Abreu-Tardelli, Lousada and Machado (2009), Medeiros (2009) and Didio (2013). The material was examined base on Bakhtin (2000). His theories about discourse genres were the main category of analysis used in this research, whose methodology is interpretative based on quantitative information for qualitative evaluations of the material and the results obtained. The main result is the observation that journalistic review, unlike what occurs in the university field, breaks with pre- established structures, although it is possible to say that its global order is roughly divided into introduction, development and conclusion. But the chain of ideas will depend much more on the knowledge about the focused object, on the professional experience and on the textual abilities of the reviewer than on the editorial rule. The exception occurs with one of two models used by Bravo! magazine that divided the text with explicit topics. The division presented variations according to the thematic content. In general, the compositional format brought this model closer to what is seen in the academic world, especially in the appreciation of books